2010
DOI: 10.1128/jcm.01256-10
|View full text |Cite
|
Sign up to set email alerts
|

Improved PCR Methods for Detection of African Rabies and Rabies-Related Lyssaviruses

Abstract: Eleven different lyssavirus species, four of which occur on the African continent, are presently recognized. These viruses cause rabies, the burden of which is highest in the developing world, where routine laboratory diagnosis is often not available. From an epidemiological and control perspective, it is necessary that diagnostic methods detect the diversity of lyssaviruses present in different regions of the world. A published and widely used heminested reverse transcription-PCR (hnRT-PCR) was evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
66
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 24 publications
4
66
0
1
Order By: Relevance
“…However, the one-step RT-PCR developed in this study demonstrated high sensitivity and specificity levels and a high value of accuracy here as well as in previously published studies (5,9,19,20,35). The method was in fact capable of detecting less than 1 TCID 50 /ml and 10 gene copies/l of the synthetic RNA of RABV.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, the one-step RT-PCR developed in this study demonstrated high sensitivity and specificity levels and a high value of accuracy here as well as in previously published studies (5,9,19,20,35). The method was in fact capable of detecting less than 1 TCID 50 /ml and 10 gene copies/l of the synthetic RNA of RABV.…”
Section: Discussionmentioning
confidence: 79%
“…A further screening of a wider panel representative of the worldwide diversity of known and emerging lyssaviruses should be applied in order to assess the performances of the method developed in this study. Improvements and subsequent revalidation of molecular diagnostic protocols should always be taken into consideration, not only for rabies but also in the cases of other viral diseases (4,5,20,30,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After sampling the bats were released. Swabs were tested for lyssavirus RNA with the use of a reverse transcription-real time polymerase chain reaction assay (Coertse et al, 2010) after total RNA extraction with the use of Trizol (Invitrogen, Carlsbad, California, USA) as described by the manufacturer. Virus-neutralizing antibodies (VNA) in serum samples were determined by a modification of rapid fluorescent focus inhibition test (RFFIT; Kuzmin et al, 2008), with DUVV2006 used as a challenge virus.…”
mentioning
confidence: 99%
“…All the specimens repeatedly tested negative by rabies virus real-time PCR. 9 Extensive investigation to determine other possible causes of viral encephalitis and bacterial meningitis did not provide the diagnosis. It was subsequently revealed that the child was also scratched on the forehead by a neighbour's dog on 29 March 2012, for which the child received no medical attention or PEP.…”
mentioning
confidence: 99%